AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE CORRS ALBUM “TALK ON CORNERS” - Sari, Dewi Wulan (Universitas Gunadarma, 2021)
Figurative language is one of the linguistic devices that are used in the writing or speech to make language more beautiful, impactful, and interesting. The researcher chooses this topic because figurative language is very unique and tricky compared to the literal language. The problems of this research are What are the figurative languages found in Talk on Corners Album by The Corrs? and What is the most dominant figurative language found in Talk on Corners Album by The Corrs?. This research has two aims, they are to find out the figurative language found in Talk on Corners Album by The Corrs and to find out the most dominant figurative language found in Talk on Corners Album by The Corrs. Qualitative method is used in this research. Perrine theory about figurative language is use to analyzed the data that were taken from Talk on Corners Album by The Corrs. The results show that 44 data were found. Out of 44 data, 13 (29,5 %) are metaphor, 2 (4,5 %) are simile, 7 (16,0 %) are personification, 3 (6,8 %) are paradox, 1 (2,3 %) are symbol, 10 (22,7 %) are into allegory, and 8 (18,2 %) are hyperbole. The most dominant figurative language found is metaphor.